A Nationwide Survey of Prostate Specific Antigen Based Screening and Counseling for Prostate Cancer. Issue 3 (May 2017) - Friedlander, David F.; Meyer, Christian P.; Choi, Kevin; Cole, Alexander P.; Hanske, Julian; Zavaski, Michael; Reznor, Gally; Sun, Maxine; Kibel, Adam S.; Lipsitz, Stuart R.; Trinh, Quoc‐Dien
Abstract : Introduction: : Controversy surrounds prostate specific antigen screening following the 2012 U.S. Preventive Services Task Force grade D recommendation. There is limited evidence evaluating patterns of prostate specific antigen counseling and patient perceptions of the prostate specific antigen test since 2012. We evaluated the association between prostate cancer screening counseling and patient sociodemographic factors in a nationally representative sample. Methods: : Using data from the 2013 Health Information National Trends Survey we identified 768 male respondents age 40 to 75 years without a prior prostate cancer diagnosis. Using logistical regression we assessed trends in prostate cancer screening, counseling and prostate specific antigen use. Results: : Overall 54.1% of respondents reported ever having a prostate specific antigen test. Men undergoing prostate specific antigen testing were more likely to have had a prior cancer diagnosis other than prostate cancer (OR 3.93, 95% CI 1.19–12.94) and to have had at least some college education (OR 11.35, 95% CI 3.29–39.04). Men 40 to 49 years old had decreased odds of undergoing prostate specific antigen testing compared to men 50 to 69 years old (OR 0.20, 95% CI 0.10–0.39). History of cancer (OR 2.50, 95% CI 1.19–5.26) was associated with greater odds of being counseled on the potential adverse effects of prostate cancer treatment. Younger men (age 40 to 49 years) had decreased odds of discussing the prostate specific antigen test with a health care professional (OR 0.32, 95% CI 0.16–0.62) and being informed of the controversy surrounding prostate specific antigen screening (OR 0.35, 95% CI 0.13–0.95). Conclusions: : We show that certain men receive substantially different prostate specific antigen screening counseling, which may impact shared patient‐provider decision making before prostate specific antigen counseling.